COPGLOW and XPS investigation of recycled metal powder for selective laser melting. (27th May 2017) - Mellin, Pelle; Shvab, Ruslan; Strondl, Annika; Randelius, Mats; Brodin, Håkan; Hryha, Eduard; Nyborg, Lars
ABSTRACT: The purpose of this paper is to compare, in terms of depth composition profile, a recycled hastelloy X powder and a virgin powder of the same alloy. We compare also the COPGLOW (compacted powder glow discharge analysis) method to the more established XPS (X-ray photoelectron spectroscopy) technique, in terms of similarity in reported elemental contents. A good match between the two methods was obtained on the surface of the powder particles (using an etching depth of 1 nm). Similar oxide layer thickness, of about 0.5–1 nm, was found on both powders by COPGLOW. Oxidation sensitive elements, such as Cr, were found on the surfaces by both XPS and COPGLOW on both powders. Surface content of Si appears to have decreased during use in selective laser melting. Finally, the two methods did not otherwise reveal any unexpected features in the depth profiles.